The Influence of Perceived Value and Product Involvement Towards Purchase Intention Mediated by Attitude - Dharma Arya Pamungkas, Dhira (Riviera Publishing, 2023)
This research aims to analyze the mediating role of consumer attitudes on the influence of perceived value and product involvement towards purchase intention. The study was conducted at a Yamaha showroom among visitors interested in purchasing a Yamaha 250cc motorcycle, with a total of 152 respondents. This quantitative research employed a survey method to gather information from the respondents. The data analysis method used in this study was Partial Least Square (PLS), utilizing the WarpPLS 8.0 program.The findings of this research indicate a significant positive influence of perceived value and consumer attitudes on purchase intention. Additionally, there is a significant direct positive influence of perceived value and product involvement on consumer attitudes. However, on the other hand, the study also reveals that product involvement does not have a significant positive or direct influence on purchase intention. The implications of this research highlight that by understanding the mediating role of consumer attitudes in the relationship between perceived value and product involvement towards purchase intention, companies can direct their marketing efforts to positively influence consumer attitudes. Furthermore, comprehending how consumer attitudes mediate the relationship between perceived value and product involvement towards purchase intention can aid companies in making more informed decisions regarding product development, marketing strategies, and customer service.